ULASAN : POLITIK SIMBIOSIS FUNGI DAN TUMBUHAN - Ivan Permana Putra (Jurnal Pro-Life, 2020)
Many mycologist believed that the successful history of plant invasion to the land was the result of co-evolutionary interaction between plant and fungi. The colonization of land by plants mainly depend on the fundamental biological evolution, among which was the symbiosis with fungi to enhance water and nutrient uptake. Untill today, most plants hold in symbioses with endophytic and mycorrhizal fungi in environment, and the consequences for plants vary broadly from mutualism to parasitism (plant fungal pathogen). Recently, scientist proved that some of those type of interactions poses dynamic situation which involving the agreement betwen host and its mycobion partner. Interestingly, the switching mechanism of the life style of the fungus from one state (mutualistic) to another( parasitic) and vice versa is potentially emerge. This review will highlight both the initial symbiosis process between plant and fungi, and how they maintain it.Keywords: Fungi, plant, symbiosis, maintenance